Delayed identification and diagnosis of Huntington’s disease due to psychiatric symptoms - Pascu, Alina Mihaela (Int J Ment Health Syst, 2015)
Huntington’s disease (HD) is a progressive neurodegenerative illness that affects 2–9/100.000 of the general population. The usual onset is at around age 35–40 years, but there were cases with onset above 55 years. The disease manifests clinically with many neurological and psychiatric symptoms, leading in advanced phases to dementia, but cognitive symptoms are frequently present much earlier in the disease course. HD is caused by an expanded polyglutamine stretch in the N-terminal part of a 350 kDa protein called huntingtin (HTT). This stretch is encoded by a trinucleotide CAG repetition in exon 1 of HTT. An expansion of greater than 36 repeats results in HD. The number of repeats is inversely correlated with the age of onset of motor symptoms, and disease onset during childhood or adolescence is associated with more than 60 CAG repeats. Mood disturbances may be one of the earliest symptoms of HD and may precede the onset of the motor pheno-type for almost 10 years. Neuropsychiatric symptoms may delay the appropriate diagnosis of HD and have major implications for disease management, prognosis and quality of life for patients and families. This case study is about a 58 years old female patient with late identification of Huntington’s disease after two admissions to psychiatric inpatient units, for the treatment of behavioral disturbances.